Resonant tunneling diode-laser diode optoelectronic integrated circuit operating as a voltage controlled oscillator - Ironside, Charlie; Figueiredo, J.; Romeira, B.; Slight, T.; Wang, L.; Wasige, E. (2009)
Recent work on an OptoElectronic Integrated Circuit (OEIC), the resonant tunneling diode-laser diode (RTD-LD) has shown that it can act as an optoelectronic voltage controlled oscillator (OVCO). The RTD-LD oscillates because of the negative differential resistance of the RTD and simply providing the RTD-LD with a dc voltage will cause it to oscillate at frequencies determined by both the external components of the circuit and the value of the dc voltage. It has been observed to oscillate at frequencies as high as 2.2GHz and be tunable from 1.8-2.2GHz as the dc voltage is tuned by 0.5V. Both monolithic and hybrid (separate RTD and LD chips) have been investigated. The hybrid RTD-LD has been accurately modeled as a Liénard's oscillator - closely related to the Van der Pol oscillator. The model is a classic of nonlinear systems theory and explains all of the observed operating features that include synchronization and chaotic output. Applications include wireless to optical signal conversion where phase synchronization has been demonstrated to transfer phase modulated signals from the wireless to the optical domain by modulating the RTD-LD OVCO to produce a phase modulated optical sub-carrier. © 2009 SPIE.